Internet Gaming Disorder and Learning Motivation of Vocational Students - Lira Erwinda; Irma Herliana Putri; Elsa Kemalia Putri; Nur Sahlami; Khairunnisa Azra Amalina; Muhammad Ahyudin; Dewi Yanah; Mohamad Asmani; Rosada Rosada (SCHOULID: Indonesian Journal of School Counseling, 2024)
The urgency of this study lies in the increasing prevalence of internet gaming disorder among students, which has begun to disrupt their focus, discipline, and motivation to learn. As excessive gaming behavior continues to rise, it poses a serious threat to students’ academic performance and personal development. Therefore, it is crucial to understand the extent of its impact on learning motivation to enable guidance and counseling teachers to design effective preventive and intervention strategies in the school setting. This study investigates the effect of internet gaming disorder on students’ learning motivation at SMK Islam PB Soedirman 1 Jakarta using a quantitative survey of 120 students. Simple linear regression analysis shows a significant negative effect (β = -0.488; p < 0.05), indicating that higher gaming addiction lowers learning motivation. Internet gaming disorder contributes 35.6% to the variance in motivation, with the remaining 64.4% influenced by other factors. These findings emphasize the importance of guidance and counseling support in preventing and addressing gaming-related motivation decline.